A modified split-Hopkinson pressure bar setup enabling stereo digital image correlation measurements for flexural testing. (March 2023) - Meyland, Martin J.; Eriksen, Rasmus N.W.; Nielsen, Jens H.
Abstract: A novel experimental setup for dynamic material characterisation that combines a ring-on-ring test configuration for equibiaxial flexural testing with a modification of the well-known split-Hopkinson pressure bar (SHPB) is presented. The design is generic, but in the present paper intended for and validated by experiments on flat circular glass samples at high strain rates. The novel modification allows an unobstructed view of a significant part of the sample's tensile surface that is made possible by replacing the conventional transmission bar with a tube through which the incident bar passes. This modification enables the application of high-speed cameras for assessing the fracture together with stereo digital image correlation (stereo-DIC) for non-contact out-of-plane displacement measurements and, at the same time, reduces the total length of the setup compared to the original design. An FE-model of the bar/tube system was generated to characterise the setup better. From that, information on strain gauge locations was extracted. Two similar experiments on glass show that the required dynamic force equilibrium could be established and that the application of high-speed cameras work as intended. Lastly, promising results were achieved from the pilot stereo-DIC measurements, indicating pure bending deflections of the sample in line with theory. Highlights: Stereo-DIC measurements in a flexural test were facilitated in a modified SHPB. The original transmission bar was replaced by a tube enabling a free sample surface. Fracture was assessed with high-speed cameras using alternating image acquisition. Measured out-of-plane displacements agreed satisfactory with plate bending theory.